Relationship between the presence of termite mounds and pasture degradation - de Lima, Sandra Santana; Alves, Bruno José Rodriques; Aquino, Adriana Maria; Mercante, Fábio Martins; Pinheiro, Érika Flávia Machado; Sant'Anna, Selenobaldo Alexinaldo Cabral; Urquiaga, Segundo; Boddey, Robert Michael (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to evaluate chemical, physical and biological indicators of degradation of pastures in areas with contrasting occurrence of termite mounds. Pasture areas with the Marandu cultivar of Urochloa brizantha (Syn. Brachiaria brizantha) were evaluated for the absence (pasture 1) or presence (pasture 2) of termite mounds, and an area of native Cerrado vegetation. The following parameters were evaluated: soil texture and fertility; soil microbial biomass; potentially mineralizable nitrogen; forage on offer; existing litter and litter deposited on the soil surface in 28 days; and free light fraction of soil organic matter. In pasture 2, termite mounds were counted and 20 nests were randomly selected for collection and identification of termites. All active mounds were inhabited by the species Cornitermes cumulans, with a mean of 128 mounds per hectare, occupying 0.1% of the net area. Among the indicators evaluated, only forage on offer and litter deposited in 28 days differed between pasture areas. The greater density of termite mounds was not related with the higher acidity of the soil or with the other evaluated parameters. The presence of termite mounds is not an indicator of the chemical and biological degradation of the pasture and is associated with the dynamics of aerial residues of Marandu palisadegrass